(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This study aimed to develop the English summative test based on high order thinking skill (HOTS) for tenth grade senior high school students. This study concerned with how to provide a product that can be an additional media for students to be easier to do an English test in final examination at school with HOTS. The development process used model proposed by Borg and Gall (1983). This study involved 30 students of X grade of math and science program at SMA N 1 Dulupi. The instruments for collecting the data were questionnaires, interview, and document analysis. The product developed has validated by the lecture of English postgraduate in Gorontalo State University, the English teacher and the students. The findings of this study are (1) The students need to get an additional media to get practice of English test with HOTS. (2) The product named “SMART (Strategy Mastery English Test)” is a product contained of questions for final examination which is appropriate based on the result of validation.